The Development of Indicators Measuring the Phenomenon of Inflation in Algeria during the Period 1990-2017 - عزري , حميد (Milev Journal of Research and Studies, 2020)
This study aims to analyze the development of the phenomenon of inflation in Algeria during the period 1990-2017 through a number of indicators, whereby the development of each of the consumer price index was tracked with a kind of focus as it is the indicator adopted in calculating the rate of inflation in Algeria, in addition to analyzing the development of each of Implicit index, monetary stability criterion and surplus demand criterion. The study found a number of results, including that the consumer price index doubled 7 times during the study period as a result of the economic reforms that led to the liberalization of a large group of commodity prices, which calls for linking any increase in wages to the increase in labor productivity.